Antioxidant Effect Potential of Garlic In Vitro and Real Food System: Effects of Garlic Supplementation on Oxidation Stability and Sensory Properties of Butter - Aydın, Serap; Tahmas Kahyaoğlu, Deren (Wiley, 2020)
AbstractIn this research, the effect of adding garlic and synthetic antioxidant to butter produced on both quality characteristics and oxidation stability during the storage (1st, 15th, 30th, 45th, 60th, 75th, and 90th days) process is investigated. With this aim, two replicates of butter samples as control, containing different proportions of garlic (butter treated with 2.5%, 5%, 7.5%, 10% crushed garlic) and with 50 ppm butylated hydroxytoluene (BHT) added are prepared. 2,2′‐Azinobis‐(3‐ethylbenzthiazoline‐6‐sulfonate) and 2,2‐diphenyl‐1‐picrylhydrazyl free radical‐scavenging ability, ferric reducing antioxidant power value of garlic are found as 26.05%; 87.48%; 70 mm mL−1, respectively. Total phenolic content, total flavonoids, and total antioxidant capacity of fresh garlic are determined. The main components of essential oil of garlic are determined. The rate of oxidation decreases as the garlic rate increases. The highest sensory analysis scores for the first days of storage are for the control and butter with 50 ppm BHT added, followed by samples with 5%, 2.5%, and 7.5% garlic added. At the end of storage, the highest sensory analysis scores are obtained by the butter with 5% garlic added. The butter with 10% garlic added is not liked in terms of sensory properties.Practical Applications: Oxidation‐causing or accelerating factors are oxygen, light, temperature, metal ions, some pigments, and degree of unsaturation. Oxidation is eliminated when these factors are eliminated. But in practice this is not possible. Therefore, it is very difficult to prevent oxidation without adding any material. Antioxidants are the most effective substances in the food industry for the production, storage, transport, and marketing of vegetable and animal fats and fat‐containing foods, delaying the effect of atmospheric oxygen at normal temperatures, preventing food spoilage, and rancidity for a certain period of time. Due to the carcinogenic effects of synthetic antioxidants, interest in natural antioxidants has increased. It is known that garlic has antioxidant effects. Natural antioxidants are used in the food industry for different purposes due to their extensive bioactivity profile. Peroxide value and thiobarbituric acid tests are generally used to determine the degree of lipid oxidation in butter.
Keywords: 2. Zero hunger